Proposal for Sets of 77Se NMR Chemical Shifts in Planar and Perpendicular Orientations of Aryl Group and the Applications - Satoko Hayashi; Waro Nakanishi (Bioinorganic Chemistry and Applications)
The orientational effect of p-YC6H4 (Ar) on δ(Se) is elucidated for ArSeR, based on experimental and theoretical investigations. Sets of δ(Se) are proposed for pl and pd employing 9-(arylselanyl)anthracenes (1) and 1-(arylselanyl)anthraquinones (2), respectively, where Se–CR in ArSeR is on the Ar plane in pl and perpendicular to the plane in pd. Absolute magnetic shielding tensors of Se (σ(Se)) are calculated for ArSeR (R = H, Me, and Ph), assuming pl and pd, with the DFT-GIAO method. Observed characters are well reproduced by the total shielding tensors (σt(Se)). The paramagnetic terms (σP(Se)) are governed by σP(Se)xx+σP(Se)yy, where the direction of nP(Se) is set to the z-axis. The mechanisms of the orientational effect are established both for pl and pd. Sets of δ(Se: 1) and δ(Se: 2) act as the standards for pl and pd, respectively, when δ(Se) of ArSeR are analyzed based on the orientational effect.